Monoclonal Antibodies and Fc‐Fusion Proteins for Pediatric Use: Dosing, Immunogenicity, and Modeling and Simulation in Data Submitted to the US Food and Drug Administration. (13th March 2019) - Liu, Xiaomei I.; Dallmann, André; Wang, Yow‐Ming; Green, Dionna J.; Burnham, Janelle M.; Chiang, Beatrice; Wu, Perry; Sheng, Mark; Lu, Kelley; van den Anker, John N.; Burckart, Gilbert J.
Abstract: The experience with the use of monoclonal antibodies and Fc‐fusion proteins (mAb/Fc) in the pediatric population is limited. The objective of this study is to review those factors impacting the clinical efficacy and product safety of mAb/Fc products in pediatric patients during drug development. We reviewed the list of biologic products in the US Food and Drug Administration's Purple Book as of March 2018 with a focus on mAb/Fc products that are indicated for use in both adults and pediatric patients. Of 68 mAb/Fc products in the Purple Book (excluding biosimilars), 20 products have approved indications in both adults and children. Thirteen products had concurrent approval for both adult and pediatric populations. The sample size of pediatric studies generally ranged from approximately 2% to 70% of the sample size of adult studies with the same indication. In general, pediatric dosing regimens were found to be more based on body weight and weight tiered than the regimens for adults. Modeling and simulation techniques comprised mainly population pharmacokinetic and pharmacodynamic models. A review of the immunogenicity incidence did not reveal any notable difference in the 5 products having data on both pediatric and adult patients. In conclusion, most of the mAb/Fc products have a different weight‐based dosing regimen for pediatric patients versus adults. An understanding of the comparative experience in drug development for mAb/Fc products between adult and pediatric patients coupled with the application of advanced modeling and simulation methods should assist future development of new mAb/Fc products for pediatric patients.